PERSIAPAN SEKOLAH DALAM MENYELENGGARAKAN PENDIDIKAN INKLUSIF UNTUK ANAK BERKEBUTUHAN KHUSUS DI SD - Zahra, Arsyafa Arienda; Winasis, Rusmalia Candra Ayu; Septyani, Rista Nurul; Minsih, Minsih (Center for Research and Community Service (LPPM) University of Abulyatama, 2025)
The purpose of this study was to describe the school's preparation in organising inclusive education for children with special needs at SD Negeri Nayubarat II, located at Jalan Majapahit, Number 21, Nusukan, Banjarsari, Surakarta City. This study used a qualitative method with the research subjects including the principal, class teachers and Special Assistance Teachers (GPK). Data collection techniques were conducted through observation, interviews, and documentation, with data validation using source triangulation and technique triangulation. The data obtained was analysed through the stages of data collection, data reduction, data presentation, and conclusion drawing. The results showed that SD Negeri Nayubarat II has made various efforts in organising inclusive education, such as providing accessible facilities, modifying the curriculum according to student needs, providing support from GPK and Shadow Teachers, conducting customised assessments, and providing equal educational facilities. However, there are still obstacles in its implementation, such as the lack of adequate facilities, the limited number of GPKs and the low level of environmental acceptance of the needs of children with special needs. To overcome these obstacles, the school continues to seek solutions through evaluation, socialisation and increasing parents' understanding. It can be concluded that SD Negeri Nayubarat II's preparation for inclusive education for children with disabilities has been quite successful, although there are still some obstacles that need to be overcome to support the sustainability of the inclusive programme.